THE WOMAN STRUGGLE OF BEING A GOVERNESS IN ANNE BRONTE’S AGNES GREY (NOBEL: Journal of Literature and Language Teaching, 2015)
In the Victorian era, the existence of governess held unique position and became a social phenomenon in England. The governess became a popular figure in fiction. Many authors of governess novels drew on their own experience as a governess. Among these authors is Anne Bronte. In her first novel Agnes Grey, she depicted the life of governess throughout its female main character named Agnes Grey. This thesis focuses on analyzing that female main character and her struggle of being a governess. The aims of the thesis are to examine the motive that leads Agnes Grey to be a governess and to reveal her struggle to face the oppression from her employers within her being of governess depicted in the novel. Since studying on woman, this thesis basically uses Feminism theory which mainly focuses on womanhood. Marxist feminism is additionally used to examine governess as working woman is as woman source of oppression. Besides, inside the analysis the thesis also tries to correlate some points with Islamic views.